2012
DOI: 10.1007/s13580-012-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grafting on growth and incidence of phytophthora blight and bacterial wilt of pepper (Capsicum annuum L.)

Abstract: Abstract. This study was conducted to investigate the effect of grafting using commercial rootstocks and breeding lines on growth and resistance to both Phytophthora blight (Phytophthora capsici) and bacterial wilt (Ralstonia solanacearum), and to evaluate the breeding lines as candidates rootstocks for grafted peppers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 16 publications
(17 reference statements)
2
28
2
3
Order By: Relevance
“…(), who observed a significant reduction of vigour in “Rebelde” chilli plants grafted on CM‐334 and by Jang et al. () on pepper plants. Similarly, Leal‐Fernández et al.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…(), who observed a significant reduction of vigour in “Rebelde” chilli plants grafted on CM‐334 and by Jang et al. () on pepper plants. Similarly, Leal‐Fernández et al.…”
Section: Discussionmentioning
confidence: 94%
“…Some authors have reported that grafting affects the development of plants, as well as the translocation of water, nutrients and hormones, which could directly affect fruit production and quality (Edelstein, Plaut, & Ben‐Hur, ; Flores et al., ; Jang et al., ). In our study, there was a lower production of flowers and leaves in grafted plants than in those not grafted on CM‐334, which coincides with that reported by García‐Rodriguez et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Source: Bolandnazar et al, 2014;Rivard et al, 2012;Keatinge et al, 2014;Onduso, 2014;Vitale et al, 2014;Hibar et al, 2006;Kaskavalci et al, 2009;Mochizuki and Yamakawa, 1979;Jang et al, 2012;Al-Chaabi et al, 2009;Rivard et al, 2010. Lee et al, (2010); Pandey and Rai (2003); Penella et al, 2014;AVRDC 2003AVRDC & 2009 The majority of users of grafted seedlings is currently greenhouse hydroponic tomato growers, whereas it is still a relatively unknown technique for open-field vegetable growers.…”
Section: Challenges In Graftingmentioning
confidence: 99%
“…Para o investimento ter retorno financeiro, o porta-enxerto não deve possuir apenas resistência a doenças, mas também deve ter compatibilidade, mantendo a produtividade e as características da cultivar utilizada como enxerto (Jang et al, 2012). De acordo com Miguel (2007), busca-se em um porta-enxerto as seguintes características: imunidade à enfermidade que se deseja prevenir; vigor e rusticidade; boas condições para realizar o enxerto; preservação da qualidade dos frutos, sem alteração de sabor; e afinidade com a planta a enxertar.…”
Section: Abstract Rootstock Compatibility For Sweet Pepper Hybrids Prunclassified